Developing an application for handyman services platform using geofencing with content-based filtering (Handy2help) / Ezzad Ab Malek … [et al.] - Ab Malek, Ezzad; Abdul Rahid @ Abdul Rashid, Nurul Najwa; Subano, Muhammad Rizzuan Ariff; Baddru'l-Sham, Ezrren Natasha; Pahruradzi, Salman (Faculty of Computer and Mathematical Sciences, 2023)
Hiring a handyman is not strange but rather the usual. People tend to hire qualified handyman services because they do not have spare time to fixing or repairing by themselves and, they do not have tools or any equipment. Moreover, the handyman services have grown widely as because of the new lifestyle which most of us are living now. Therefore, the project aims to design and develop a platform to connect the handymen and users who need the services. Handy2Help can help handymen to looking for a job by using geofence technology. Geofence technology is used to send out the notification to potential handymen that are available for the job in the area within the geofence boundary. This mobile application will focus on helping handymen to have better job opportunity and a user who are looking for handyman services within Jasin and Merlimau, Melaka. This application has been tested using functionality testing to evaluate the effectiveness and functionality.